The Impact of Demographic Factors on Student Attendance in Queensland State Secondary Schools - O'Connor, Mike (Australian and International Journal of Rural Education, 2021)
This article analyses the impact of three demographic factors on student attendance 0ver a three-year population level statistical analysis of student attendance rates in Queensland (Australia) state secondary schools. Whole school attendance rates were mapped against the demographic factors of schools’ Index of Community Socio-Educational Advantage (ICSEA) values, proportion of Indigenous students within the school, and school population size as independent variables to identify which schools recorded the highest student attendance as measured by proportion of students with more than 95 per cent average attendance across the years 2014-2016. The geographic and demographic profile of these schools were then assessed to guide direction for future research. The data from this sample of schools indicates no significant relationship between high levels of student attendance and the three independent variables. Subsequent analysis of school location resulted in identification of a significant number of schools in rural locations attaining excellent attendance rates against both study sample schools and state benchmarks. It is evident that several schools have successfully navigated what might be considered challenging school demography to attain higher than average attendance rates. Despite the age of this data, no significant system-wide attendance improvement is presently evident, and the same conditions of challenge remain for schools. The findings suggest a need for a more forensic approach to analysis of school climate and culture to determine factors contributing to student attendance. The data from this sample of schools indicates no significant relationship between high levels of student attendance and the three independent variables, challenging long held assumptions that low socio-economic status and high proportion of indigeneity are significant causal factors for low rates of school attendance. Subsequent analysis of school location resulted in identification of a significant number of schools in rural locations attaining excellent attendance outcomes against both study sample schools and state benchmarks. It is concluded that rather than relying on traditional stereotypes of school demography influencing perception of student attendance patterns, educators must adopt a more forensic approach to analysis of their school climate and culture to determine contributing factors to student attendance excellence. ICSEA is a scale that applies a numerical value to schools in Australia determined by the level of educational advantage experienced by students in the school. ICSEA considers parental occupations, parental level of education, school geographical location and the proportion of indigenous students in the school. An ICSEA of 1000 is the average benchmark value (ACARA, 2014)